Building an Adaptive and Sustainable Human Resource Information System in the Digital Age - Aulia, Siti (West Science Journal Economic and Entrepreneurship, 2025)
The digital age has redefined the role of Human Resource Information Systems (HRIS) from a traditional administrative tool to a strategic enabler of organizational success. This study presents a systematic literature review of 35 scholarly documents sourced from Google Scholar to examine how HRIS can be designed to be both adaptive and sustainable in the context of digital transformation. The findings highlight three core themes: adaptability, sustainability, and digital integration. Adaptability reflects HRIS responsiveness to dynamic business environments, workforce diversity, and crises such as the COVID-19 pandemic. Sustainability emphasizes the alignment of HRIS with environmental, social, and governance (ESG) principles, ensuring ethical, inclusive, and long-term value creation. Digital integration illustrates the growing adoption of advanced technologies such as artificial intelligence, big data, cloud computing, and blockchain to enhance HR efficiency and decision-making. The study concludes that the future of HRIS lies in balancing technological innovation with human-centered values to achieve agility, inclusivity, and resilience. It contributes to the discourse on digital HR transformation by mapping key themes, identifying research gaps, and offering practical and policy recommendations for organizations seeking to build adaptive and sustainable HRIS frameworks.